THE EFFECT OF NURSERY RHYMES ON STUDENTS’ VOCABULARY ACHIEVEMENT AT THE FIFTH GRADE OF SDN 10 POASIA - Angriana, Ella; Suhartini, Lelly; Agustina, Sitti (Journal of Teaching of English, 2020)
This study is conducted to investigate the effect of using nursery rhymes on students’ English vocabulary (noun and adjective) achievement at fifth grade of SDN 10 Poasia. This study applied pre-experimental design with one group pre-test and post-test design. The population of this study was all of V grade of SDN 10 Poasia consisting of 67 students. Technique of taking sample of this study was purposive sampling involving 21 students. Vocabulary achievement test in the form of multiple choices consisting of 37 numbers was used as instrument of this study. The result showed that there was a significant effect of using nursery rhymes in improving students’ English vocabulary achievement. It was proven by the improvement of students’ mean score from pre-test to post-test. The mean score for pre-test was 34.81 and the mean score for post-test increased to 76.81. It was supported with the result of t-test, the value of Sig. (2-tailed) was 0.000 with α = 0.05. H1 was accepted because the value of Sig. (2-tailed) was below α value. It means that there was a significant effect of using nursery rhymes on students’ English vocabulary achievement of the VB students’ of SDN 10 Poasia.